PENGARUH KONSERVATISME AKUNTANSI, KEPEMILIKAN MANAJERIAL DAN UKURAN DEWAN KOMISARIS TERHADAP TAX AVOIDANCE - Pramudito, Batara Wiryo; Ratna Sari, Maria M (E-Jurnal Akuntansi, 2015)
Tax avoidance is a legal way to reduce the tax burden. Tax avoidance can measured with cash effective tax rate (CETR). The purpose of this study is to giving information about the impact of accounting conservatism, managerial ownership and board size to tax avoidance. This research was conducted at manufacturing companies listed on Indonesian Stocks Exchanges on 2010 – 2013. Sampling method in this study is purposive sampling method. The data on this study analyzed with multiple linier regression analysis. Based on the analysis that has been done, this study prove that accounting conservatism and board size has no impact to tax avoidance, while managerial ownership has a negative impact to tax avoidance.
Keywords: Accouting Conservatism, Managerial Ownerships, Board Size, Tax Avoidance, Cash Effective Tax Rate